Encouraging the Creation of New Business Innovations and Growing New Entrepreneurs Through Hobby-Based Entrepreneurship Training as a Source of Income - Farida, Elis Anita; Mohammad Fathoni; Zessicha Belliana Putri; Suryo Hadi Kusumo; Tri Dina Fitria; Arifin, Muhammad; Kusyairi, Imam (⁠International Journal of Asia Pacific Community Service, 2024)
Hobby-based entrepreneurship has become a potential strategy to encourage the creation of new business innovations and grow young entrepreneurs in Indonesia, especially in the Krian area, Sidoarjo, East Java. Hobby-based entrepreneurship training aims to identify market opportunities, strengthen business ideas, and teach product innovation and digital marketing to participants. The training method is carried out through a structured approach that includes theory and practice, focusing on three main aspects, namely identifying business potential from hobbies, strengthening business ideas, and using digital platforms for marketing. The results of the training showed that participants were able to identify market opportunities from their hobbies, such as handicrafts, culinary, and graphic design. The use of digital platforms such as Instagram, Shopee, and TikTok has proven effective in reaching a wider market. In addition, participants also succeeded in developing product innovations and diversifying to increase business competitiveness. However, several challenges such as limited access to capital and digital skills are still obstacles to long-term business development. This training provides in-depth insight into the potential of hobby-based entrepreneurship as a source of income, as well as highlighting the importance of strengthening digital marketing capacity and product innovation to achieve business sustainability. Based on adequate infrastructure support and ongoing mentoring, this initiative has great potential to create new, competitive entrepreneurs.